Introduction to modern power electronics - Trzynadlowski, Andrzej (John Wiley & Sons, Inc., 2016)
This book constitutes a comprehensive overview of the modern power electronics. Various semiconductor power switches are described, complementary components and systems are presented, and power electronic converters that process power for a variety of applications are explained in detail. This third edition updates all chapters, including new concepts in modern power electronics. New to this edition is extended coverage of matrix converters, multilevel inverters, and applications of the Z-source in cascaded power converters. The book is accompanied by a website hosting an instructor’s manual, a PowerPoint presentation, and a set of PSpice files for simulation of a variety of power electronic converters.